전개형 메쉬 안테나 구조물과 메쉬 원단 간 클램핑 체결기법의 유효성 검증 시험 및 분석 - 박정수(Jung-Soo Park); 채봉건(Bong-Geon Chae); 오현웅(Hyun-Ung Oh) (항공우주시스템공학회지, 2024)
Recently, both volumes and weights of antennas are increasing because of advancement of satellite missions. Research studies on mesh deployable antennas that can be highly stowable and lightweight are also increasing. When a deployable mesh antenna is subjected to repeated deployment tests on the ground, vibration of launch environments can cause slip between the antenna structure and the mesh fabric, resulting in failure to maintain the surface curvature of the antenna and Openning Per Inch (OPI). Such failure is the main cause of RF performance and mission capability degradation. Thus, studying a fastening technique to prevent slip between the antenna structure and mesh fabric is essential. This study proposed a Clamping fastening technique using rivets between the antenna structure and the mesh fabric. To evaluate the fastening efficiency of the Clamping fastening technique, tensile tests were conducted according to antenna structure type and rivet increment. Results were analyzed and fastening efficiency of the proposed clamping fastening technique was verified. 최근 위성의 임무 고도화로 인하여 안테나의 부피 및 무게가 증가하고 있으며, 높은 수납효율과 초경량화 구현이 가능한 전개형 메쉬 안테나에 대한 연구가 급증하고 있다. 전개형 메쉬 안테나는 지상에서 반복 전개 시험 및 발사 진동 환경 아래서 안테나 구조물과 메쉬 원단 간 Slip 현상이 발생하게 되어 안테나 반사면의 곡률 유지 및 OPI 유지를 실패할 수 있으며, 이는 RF 성능 및 임무 수행 능력을 저하시키는 주된 원인이 된다. 이로 인해 안테나 구조물과 메쉬 원단 간 체결기법에 대한 연구는 필수적이며, 따라서 본 연구에서는 안테나 구조물과 메쉬 원단 간 Clamping 체결기법을 제안하였다. 위 기법의 체결성을 평가하기 위해 안테나 구조물의 형태 및 체결 포인트 증분에 따라 인장시험을 진행하였으며, 각 인장시험의 결과를 분석하여 제안한 Clamping 체결기법의 유효성을 검증하였다.